The Effect of Dialogue Journal upon the Writing Achievement of the 8th Grade Students of SMP N 3 Banjar in the Academic Year of 2014/2015 - ., Ni Putu Oktaviana Dewi; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA; ., Dra. Luh Putu Artini, MA., Ph.D. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Tujuan dari penelitian ini adalah untuk mengetahui ada atau tidaknya bebedaan berarti dalam kemampuan siswa menulis antara siswa yang diajar menggunakan strategi Dialogue Journal dengan siswa yang diajar menggunakan strategi konvensional. Penelitian ini menggunakan metode Post-test Only Control Group Design. Populasi dari penelitian ini adalah siswa kelas 8 SMP N 3 Banjar. Metode Cluster Random Sampling digunakan untuk menentukan sample dari penelitian ini. Kelas VIII.5 dipilih sebagai kelompok experimental yang diajar menggunakan strategi Dialogue Journal, sedangkan kelas VIII.3 dipilih sebagai kelompok kontrol yang diajar menggunakan strategi konvensional. Hasil dari pengolahan data menunjukkan bahwa siswa kelompok experimental menunjukan keterampilan menulis lebih baik dibandingkan dengan siswa kelompok kontrol. Hal ini dibuktikan dari analisis deskriptif yang menunjukan nilai rata-rata siswa kelompok experimental adalah 75.83, sedangkan nilai rata-rata siswa di kelompok kontrol adalah 62.46. Hasil dari t-test juga menunjukkan bahwa nilai tobs lebih besar dari nilai tcv. Nilai dari tobs adalah 7.256, sedangkan nilai dari tcv adalah 2.02 (α = .05). Ini berarti bahwa terdapat perbedaan yang berarti antara siswa yang diajar menggunakan strategi Dialogue Journal dengan siswa yang diajar menggunakan strategi Conventional.Kata Kunci : Strategi Dialogue Journal, Strategi konvensional, kemampuan menulis This study aimed at investigating whether or not there was a significant difference in writing competency between the students who were taught by using dialogue journal strategy and those who were taught by using conventional strategy. The research design of this study was Post-test Only Control Group Design. The population was the eighth grade students of SMP Negeri 3 Banjar. Cluster Random Sampling was assigned to select the sample of the study.Class VIII.5 was assigned as the experimental group which was taught by using Dialogue Journal Strategy and class VIII.3 as the control group which was taught by using conventional strategy.The result of the data analysis showed that students in experimental group perfomed better writing than students in control group. It was proven by the result of descriptive statistics that showed the mean score the experimental group was 75.83, while the mean score of control group was 62.46. The result of the t-test also showed that the value of the tobs was higher than the tcv. The value of the tobs was 7.256, while the value of the tcv was 2.02 (α = .05). It means that there is a significant difference in writing competency between students who were taught using dialogue journal with students who were taught using conventional strategykeyword : Dialogue Journal Strategy, Conventional Strategy, writing competence